Sarcoidosis during etanercept treatment for rheumatoid arthritis in women with a history of bilateral oophorectomy - Sawahata, Michiru; Sigiyama, Yukihiko; Yamasawa, Hideaki; Miki, Atsushi; Yamamoto, Hisashi; Muto, Shigeaki; Yamamoto, Hironori; Bando, Masashi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
nd in immune-mediated inflammatory diseases, such as rheumatoid arthritis (RA). Paradoxically, this treatment induces sarcoidosis in a small population of RA patients as a class effect. A safer anti-TNF therapeutic strategy requires understanding of the risk factors for sarcoidosis. In Japan, TNF inhibitor was introduced in 2003. We reviewed 226 consecutive patients (65 men and 161 women) who were newly diagnosed with sarcoidosis between 2003 and 2012 at Jichi Medical University Hospital, Japan. We detected 3 cases in which sarcoidosis developed during etanercept treatment for RA. All 3 cases were women who had undergone bilateral oophorectomy more than 20 years earlier. Taken together with our previous epidemiologic findings of a consistently maintained second peak after menopause in the age-specific distribution of sarcoidosis in women over four decades, long-term insidious ovarian dysfunction was a possible risk factor for sarcoidosis under certain conditions, especially during etanercept treatment.